Two birds with one stone: can green finance drive the circular economy? - Pengyu Chen; QianYing Chen (Humanities & Social Sciences Communications)
Abstract In practice, the implementation of a circular economy often encounters market failures. Can government intervention, as proposed in Enns’ theory, help mitigate these failures? To address this question, this study examines the relationship between green finance and the circular economy using data from 279 Chinese cities between 2006 and 2021. The findings reveal that green finance significantly promotes the development of the circular economy. Second, green finance fosters circular economy growth primarily by increasing social lending and driving innovation. Third, the impact of green finance on the circular economy is more pronounced under stringent environmental regulations, heightened public awareness of environmental issues, and lower pollution levels. Fourth, green finance exhibits positive spatial effects, meaning it benefits both local and neighboring cities’ circular economies. Finally, the green finance-driven circular economy contributes to carbon neutrality. This study evaluates the effectiveness of green finance and offers policy recommendations for advancing green finance and circular economy development in China and other developing countries.